Convergence of Islamic Law and Customary Law in Melinting Lampung Traditional Marriage - M. Shofwan Taufiq; Adhimaz Kondang Pribadi (Budapest International Research and Critics University, 2022)
The law is all regulations which contain regulations that must be obeyed by everyone and there are strict sanctions in it for those who violate it. The purpose of this study was to obtain a specific description of one of the phenomena of marriage among the people of Lampung Keratuan Melinting. The interaction discourse between Islamic law and customary law is not a phenomenon that will present numerical data, so it cannot be investigated directly and cannot be summed with simple measuring tools. Thus the quantitative method cannot be used, because it does not pretend to solve the problem. Non-traditional marriages performed among indigenous peoples are substantially not much different from marriages performed by people who are not bound by customary rules. The difference is that in its implementation, non-traditional marriages still have to be approved by the customary balancers.